1993
DOI: 10.1007/bf00042355
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a proline-rich mRNA that accumulates during pod development in oilseed rape (Brassica napus L.)

Abstract: Pod development in oilseed rape (Brassica napus) culminates in a process known as dehiscence (shatter) which can result in the loss of seed before the crop is harvested. In order to investigate the biochemical and the genetic basis controlling this process, a cDNA library was constructed from the dehiscence zone of developing pods. This resulted in the isolation of a cDNA clone (SAC51). The mRNA encoded by SAC51 had a transcript size of ca. 700 nucleotides and was found, by northern analysis, to accumulate pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 44 publications
3
38
0
Order By: Relevance
“…All of these proteins possess a distinct hydrophobic domain of 80 to 100 amino acids encompassing eight regularly spaced Cys residues. Transcripts encoding hybrid proteins have been isolated from many different plant species under conditions of cold (Castonguay et al, 1994), high salt (Deutch and Winicov, 1995), mechanical stress (Huang et al, 1998), or tissue-specific selection (Josè-Estanyol et al, 1992;Coupe et al, 1993;Yasuda et al, 1997). Ascribing functional roles to these proteins has been difficult and in no case has a protein of this type been associated with a phenotypic character.…”
Section: Discussionmentioning
confidence: 99%
“…All of these proteins possess a distinct hydrophobic domain of 80 to 100 amino acids encompassing eight regularly spaced Cys residues. Transcripts encoding hybrid proteins have been isolated from many different plant species under conditions of cold (Castonguay et al, 1994), high salt (Deutch and Winicov, 1995), mechanical stress (Huang et al, 1998), or tissue-specific selection (Josè-Estanyol et al, 1992;Coupe et al, 1993;Yasuda et al, 1997). Ascribing functional roles to these proteins has been difficult and in no case has a protein of this type been associated with a phenotypic character.…”
Section: Discussionmentioning
confidence: 99%
“…The insert was Gelase (Epicentre, c/o Cambio, Cambridge, UK) extracted from low-melting-point agarose (FMC products, Rockland, Me., USA) and labelled using the method of nick-translation (Rigby et al 1977). The blots were hybridized and washed as described in Coupe et al (1993) except that the senescing leaf Northern blot was hybridised at 42~ in a hybridisation buffer that contained 50% formamide and the final wash was at 42~ in 1 • SSPE (Sambrook et al 1989…”
Section: Methodsmentioning
confidence: 99%
“…The probes were synthesized using the method of Picton et al (1993b) and used to screen 150000 recombinant plaques plated on 3 plates of 50 000 each. Replicate lifts were probed and hybridized as described in Coupe et al (1993). Plaques which differentially hybridized to the abscission-zone cDNA probe were re-screened at lower densities.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of hydrolytic enzymes including β-1,4-glucanase and polygalacturonase involved in cell separation in the DZ appears to be regulated by auxin (Coupe et al, 1993). Chauvaux et al (1997) observed that a decrease in auxin content in the DZ just prior to moisture loss in siliquae was correlated with a tissue specific increase in β-1,4-glucanase activity and hence with siliqua dehiscence.…”
Section: Biochemical and Molecular Mechanisms Underlying Shatter Resimentioning
confidence: 99%
“…Molecular studies of dehiscence zone specific mRNAs have led to isolation of genes which have been considered to be involved in production and regulation of enzymes involved in degeneration of the separation layer upon siliqua ripening (Coupe et al, 1993(Coupe et al, , 1994Petersen et al, 1996;Whitelaw et al, 1999). In Arabidopsis, seed shattering is controlled by the several MADS-box and homeodomain genes.…”
Section: Inheritance Of Shatter Resistancementioning
confidence: 99%